The Verb â€œTo Cutâ€ in Nias Middle Dialect: The Study of Natural Semantic Metalanguage (NSM) - Fransiskus Ndruru; I Wayan Budiarta; Ni Wayan Kasni (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2021)
Nias middle dialect is one of dialects used by people living on Nias island that administratively belongs to North Sumatra Province of Indonesia. The lack of studies on the language especially in semantics field was the main motivation in conducting this research. Another thing that also strongly supported the conduct of this research was a phenomenon in which some verbs semantically related to verb 'to cut' were rarely used by speakers of Nias middle dialect. Therefore, this study was conducted with the aims of discovering the verbs that have semantic relation to the verb â€œto cutâ€ and describing the meaning of the verbs by employing the Natural Semantic Metalanguage theory of Wierzbicka (1996) in the qualitative research design. To collect the data, cakap method was applied which is supported by pancing and rekam techniques. In analyzing the data, padan method was applied. Based on the results of data analysis, it was revealed that there were forty-seven Nias middle dialect verbs that semantically related to the verb 'to cut'. In accordance with the results of the explication of meaning, the verbs can be classified into three groups, namely verbs that are done with tools, verbs that are done without tools, and verbs that can be done with or without tools. This phenomenon shows that Nias people do a lot of cutting activities in their social lives.